Gaya Kepemimpinan Kepala Sekolah dalam Membentuk Sekolah Berbasis Islam di SMPI PK Muhammadiyah Delanggu - Faizah, Nabilla; Azani, Mohammad Zakki (Jurnal Ragam Pengabdian, 2026)
The development of Islamic-based schools requires principals who can integrate effective leadership with Islamic values to foster a supportive learning environment and strengthen students’ character. This study aims to analyze the principal’s leadership style in developing an Islamic-based school at SMPI PK Muhammadiyah Delanggu. This research employed a qualitative approach using a descriptive case study design. Data were collected through interviews, observations, and documentation and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the principal applies democratic, visionary, transformational, and Islamic leadership styles. Democratic leadership is reflected in participatory decision-making and transparent management. Visionary leadership is demonstrated through innovative programs, including Tahsinand Tahfiz Al-Qur’an, Esmide Got Talent (EGT), the English Communication Program (ICP), and psychological counseling services. Transformational leadership encourages teacher motivation, collaboration, and continuous school improvement. Islamic leadership is embedded in the school culture through regular religious activities and character education based on Islamic values. Although challenges remain, including differences in teachers’ religious commitment, students’ character development, and parental understanding, these are addressed through participatory and value-based leadership. The study concludes that integrating these leadership styles effectively strengthens Islamic school culture and supports students’ academic, moral, and spiritual development.